Дистанційна інфрачервона термографія як допоміжний метод у діагностиці та моніторингу поопераційних стенозів гортані - Паламарчук, В. О.; Войтенко, В. В.; Котовський, В. Й.; Дунаєвський, В. І. (Clinical Endocrinology and Endocrine Surgery, 2013)
We have examined prospectively 34 patients after thyroidectomy. The control group consisted of 18 patients without postoperative complications. The main group consisted of 16 patients from the group (7 patients) with transient unilateral paresis of the larynx, the group (3 patients) with unilateral postoperative paralysis of the larynx, and a group of 6 patients with laryngeal reinnervation surgery performed. The survey was conducted on the postoperative stage and included remote the infrared thermography (RIT) of the front of the neck, videolaryngoscopy. Average follow-up was 7,98±1,04 months. Analysis of the RIT results in the postoperative period in the control group and in the groups showed thermoasymmetry ∆T=0,16±0,06°C, the group of patients with transient of the larynx paresisand a group of patients after surgery laryngeal reinnervation had thermoasymmetry records ∆T=0,19±0,03°C and 0,23±0,03°C respectively. A group of patients with unilateral paralysis of the larynx had ∆T=3,4±0,16°C, which is statistically significantly different from the group with the physiological norm. The difference between the temperature indicators on symmetrical regions of the larynx during transient paresis larynx and after reinnervation and temperature indicators without postoperative complications is statistically not significant. The temperature gradient is statistically significant by the permanent. paralysis of the larynx. Remote infrared thermography as a subsidiary method can be applied and gives a visual information about the metabolic disturbances in neuropathic stenosis of the larynx.